PENINGKATAN HASIL BELAJAR PENDIDIKAN AGAMA KATOLIK SISWA KELAS XI MIA DI SMAK ST. YAKOBUS RASUL LEWOLEBA DENGAN MENGGUNAKAN METODE DISKUSI KELOMPOK - Maria Elisabeth Wesan Raring; Yohanes Maria Vianey Benolo Watun (CV. ADIBA AISHA AMIRA, 2025)
This research aims to improve the learning outcomes of students in class XI MIA SMAK St. James Rasul Lewoleba through the discussion method. This type of research is Kleas Action Research (PTK). The location of this research is at SMAK St. James Rasul Lewoleba, East Lewoleba Village, Lembata-NTT Regency. The students of this study are students of class XI MIA with a total of 17 students and teachers as researchers or observers, this research was carried out in September 2024. The data collection techniques used are observation, tests, and interviews. The results of this study show that in cycle 1, teacher activities get an average score of 2.49 with a fairly good category, student activities get a total score of 32, and an average score of 2.46 with a fairly good category. Then in the second cycle, teacher activities obtained a total score of 66, and an average score of 3.3 with a very good category. Meanwhile, the students' activities received a total score of 51, and an average score of 12.75 with a very good category. The learning outcomes of students in cycle 1 obtained a completeness score of 35% with an incomplete score of 64%. Meanwhile, the learning results in cycle II obtained a 100% completeness score. Thus, it can be concluded that there is an increase in student teaching results by using the kelmpok discussion method in class XI MIA SMAK St. James Rasul Lewoleba.